Insights into the removal of organic contaminants by calcium sulfite activation with Fe(III): Performance, kinetics, and mechanisms. (1st August 2022) - Zhou, Zhengyuan; Huang, Jingyao; Zeng, Guilu; Yang, Rumin; Xu, Zhiqiang; Zhou, Zhikang; Lyu, Shuguang
Highlights: CaSO3, slow-released SO3 2− source, was introduced in S(IV)-based AOPs. Fe(III)/CaSO3 system was established for the removal of various organic contaminants. The major ROS, contaminants degradation mechanism, and pathways were revealed. The degradation performance of contaminants in complex solution matrixes was investigated. Extensive applications and broad-spectrum of Fe(III)/CaSO3 system were demonstrated. Abstract: S(IV)-based advanced oxidation process has been applied for contaminants remediation. However, as a traditional source of sulfite (SO3 2− ), Na2 SO3 is extremely soluble in water, resulting in a high concentration of SO3 2− to quench the generated reactive oxygen species (ROS). In this work, CaSO3 was introduced instead of Na2 SO3 for its slow-released SO3 2− ability and Fe(III)/CaSO3 system was established for the removal of trichloroethylene (TCE) and other organic contaminants. The degradation efficiency of TCE reached 94.0% and TCE could be completely dechlorinated and mineralized, while the removal of other contaminants was all over 85.0% at the optimal tested conditions. Through EPR detection, ROS scavenging and probe tests, and quantification of ROS amounts, it was concluded that the dominant ROS in Fe(III)/CaSO3 system were SO4 − · and 1 O2, of which the transformation mechanism of SO4 − · to 1 O2 was revealed and demonstrated comprehensively. The synergistic contaminants degradation performance in different sulfur-iron-containing systems and in the presence of oxidants was evaluated. The effects of various solution conditions were assessed and Fe(III)/CaSO3 system was of higher resistance on complex solution matrixes, suggesting the broad-spectrum and application perspective for the remediation of complex contaminants in actual water.